Analisis Metakognitif Siswa dalam Pemecahan Masalah Segiempat pada Siswa SMP - Susanti, Aprilia, Masduki, S.Si, M.Si (2016)
Students have to use metacognitive problem solving quadrilateral because there is a correlation between metacognitive and problem solving. This study aims to describe aspects of metacognitive skills of planning, monitoring, evaluation in problem solving quadrilateral. This research is a qualitative research. The duration of the studies in the second semester of the 2015/2016 academic year. Subjects in this study were class VII C SMP N 1 Gatak totaling 32 students. The technique of collecting data are using the test method, interviews, observation, and documentation. Data validation was done by triangulation method by comparing the test data, interviews, observation and documentation. Data analysis technique conducted in stages, data reduction, data presentation, verification and conclusion. The results obtained by students with high ability can use metacognitive skills to the maximum, the students with the ability're not using metacognitive skills to the maximum, on students with low ability not use metacognitive skills to the fullest.